2022
DOI: 10.1007/s40037-022-00721-z
|View full text |Cite
|
Sign up to set email alerts
|

Early career experiences of international medical program graduates: An international, longitudinal, mixed-methods study

Abstract: Introduction Increasingly medical students pursue medical education abroad. Graduates from International Medical Programs (IMPs) practice globally, yet how to prepare students for an unknown international environment is complex. Following IMP graduates throughout their early careers, this study offers insights into gaps in current undergraduate education. Methods In this international, longitudinal, mixed-methods study, 188 graduates from seven IMPs comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It serves to identify university medical schools contributing to the outcome of excellence in the medical education [19] of doctors who have subsequently become award-winning clinicians. Naturally, the information we provide will be of importance to current and future graduates from International Medical Programs [20] as well as local prospective medical students.…”
Section: Lmc Merit Awards and Uk Medical Schoolsmentioning
confidence: 99%
“…It serves to identify university medical schools contributing to the outcome of excellence in the medical education [19] of doctors who have subsequently become award-winning clinicians. Naturally, the information we provide will be of importance to current and future graduates from International Medical Programs [20] as well as local prospective medical students.…”
Section: Lmc Merit Awards and Uk Medical Schoolsmentioning
confidence: 99%
“…Another common critical frame is that IMPs are "an opportunity for students who will otherwise "miss out" on medical education due to the compe[ti]tiveness of American and Canadian medical schools" (Morgan et al, 2017). In a previous project, we found that IMPs are indeed a popular choice for those who cannot or choose not to study medicine in their home country (Brouwer et al, 2022). Yet, these students not only benefit; many face significant intercultural challenges or even rather hostile rhetoric from other doctors and the public (Ho et al, 2015) upon graduation and returning to their home country.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, IMPs have been found to offer an opportunity for students who cannot or choose not to study medicine in their home country . Notably, with more than 70% of their graduates practicing abroad, IMPs essentially prepare their students for a career elsewhere (Brouwer et al, 2022). Scholars have critiqued this perceived commercial model and the applicability of IMP curricula to other health care systems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation